Indentation-induced crack interaction in alumina ceramics - Twigg, P; Davidge, R; Riley, F; Franco, A; Roberts, S (1996)
Polycrystalline aluminas of tailored composition and grain size, prepared using liquid-phase sintering aids based on the Al2O3-CaO-SiO2 and Al2O3-MgO-SiO2 systems, have been indented at loads close to their critical fracture limit P*, using closely spaced arrays of low-load Vickers indentations. The propagation of cracks caused by indentation is influenced by internal residual stresses at alumina grain boundaries developed during cooling from the processing temperature, and primarily the result of thermal expansion mismatches between the alpha-Al2O3 crystals of the matrix and an intergranular glass of composition related to that of the sintering aid. The Al2O3-MgO-SiO2 system gives a glass of significantly lower expansivity than alpha-Al2O3; hoop tensile stresses are generated at the alumina-alumina boundaries which assist microcrack propagation and the interlinking of lateral cracks from the closely spaced indentations. The converse is the case for the Al2O3-CaO-SiO2 system, giving a glass of slightly higher expansivity than alumina, and which generates compressive stresses suppressing crack interlinking. Indentation arrays provide a useful technique for modelling the processes occurring during erosive wear caused by hard particle impact.